KONDISI MASYARAKAT YANG MENGKONVERSI LAHAN PERTANIAN DI NAGARI SUNGAI NANAM KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Nora, Mesi Elfia; Juita, Erna; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
ABSTRACTThis study aimed to describe the data on Nagari Sungai Nanam Kecamatan Lembah Gumanti Kabupaten Solok distric.: 1. Communities living conditions in villages who convert agricultural land. 2. Level of asset ownership. 3. Number of family members who convert agricultural land. This type of research is a descriptive study and the sample in this study was 314 house holds taken using purposive sampling technique with a proportion of 25%, so the sample size is 80 house holds. This study is using a questionnaire. The result of the study are: 1. The living conditions that convert agricultural land not adequate because the vast house owned as many as 20 m3 of 48 people (60%). This is not in accordance with the criteria of the ideal size and healthy home for occupied . 2. The level of community ownership of assets that convert agricultural land in villages is reduced 47 people (58.75%). 3. Number of family members of people who convert agricultural land in villages is the trigger conversion of agricultural land into housing as many as 42 people (52.5%).